W rozmównicy, przez kratę, pod kontrolą - regulacje zwyczajowe i prawne niektórych aspektów komunikacji nieoficjalnej zakonnic klauzurowych = In the parlour, through the bars, under supervision: Customary and legal regulations of selected aspects of enclosed nunc` unofficial communication - Borkowski, Igor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the analysis presented in the paper are external regulations regarding place, time and means of getting involved in primarily private spoken communication by nuns. The regulations, which are nowadays somewhat relaxed, used to be very strict in the community of enclosed nuns.
Keywords: komunikacja językowa; język mówiony; zakonnice; klauzura; language communication; spoken language; nuns; enclosed religious orders